1996
DOI: 10.1016/s0167-4889(96)00076-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haloperidol on the sarcoplasmic reticulum Ca-dependent adenosine triphosphatase

Abstract: Several effects of the neuroleptic agent haloperidol on the sarcoplasmic reticulum (SR) Ca-dependent adenosine triphosphatase (Ca-ATPase) and Ca transport are described. Haloperidol inhibits the Ca-ATPase activity in the presence of calcimycin. The effect depends on the conditions of preexposure of the membranes to the drug: the inhibition increases with the preincubation time; Ca and Mg protect the enzyme against the effect of the drug. The inhibitory effect of haloperidol decreases upon increasing [Ca2+], at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…It has been previously reported that several hydrophobic drugs interact with the catalytic site in the E 2 enzyme form, tying up the entry of Pi (De Meis et al 1988;Wolosker et al 1992;Takara and Alonso 1996). The present results support a similar interpretation for the effects of carticaine on the Ca 2+ -ATPase.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It has been previously reported that several hydrophobic drugs interact with the catalytic site in the E 2 enzyme form, tying up the entry of Pi (De Meis et al 1988;Wolosker et al 1992;Takara and Alonso 1996). The present results support a similar interpretation for the effects of carticaine on the Ca 2+ -ATPase.…”
Section: Discussionsupporting
confidence: 88%
“…The inhibitory effect of carticaine on the ATPase activity does not depend on the preexposition of the SR membranes to the local anesthetic; preexposition to neither Ca 2+ nor Mg 2+ protects the Ca 2+ -ATPase from the inhibitory action of carticaine, as reported for other hydrophobic agents (Takara and Alonso 1996).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Ca-ATPase activity increased when [Mg 2+ ] was increased until it reached a maximal value (Fig. 3B) and was then inhibited at higher concentrations, as described for the Ca-ATPase isolated from other muscle tissues (Takara and Alonso, 1996).…”
Section: Discussionsupporting
confidence: 64%